Lycopene in the prevention of renal cell cancer in the TSC2 mutant Eker rat model - Şahin, Kazım; Cross, Brian; Şahin, Nurhan; Ciccone, Karina; Suleiman, Shadeah; Osunkoya, Adeboye O.; Küçük, Ömer (Elsevier Science Inc, 2015)
Renal cell carcinoma (RCC) is the most frequent upper urinary tract cancer in humans and accounts for 80-85% of malignant renal tumors. Eker rat represents a unique animal model to study RCC since these rats develop spontaneous renal tumors and leiomyoma, which may be due to tuberous sclerosis 2 (TSC2) mutation resulting in the activation of the mammalian target of rapamycin (mTOR) pathway. This study examines the role of a lycopene-rich diet in the development of RCC in the TSC2 mutant Eker rat model. Ten-week old female Eker rats (n = 90) were assigned in equal numbers to receive 0, 100 or 200 mg/kg of lycopene as part of their daily diet. After 18 months the rats were sacrificed and the kidneys were removed. Immunohistochemical staining with antibodies against mTOR, phospho-S6 and EGFR were performed, as well as hematoxylin-eosin staining for histologic examination of the tumors. Tumors were counted and measured in individual kidneys. Presence of tumor decreased from 94% in control animals to 65% in the experimental group, but the difference was not statistically significant (P < 0.12). However, mean numbers of renal carcinomas were statistically significantly decreased in the lycopene-treated rats (P < 0.008) when compared to untreated controls. In the lycopene group, tumor numbers decreased (P < 0.002) and the numbers tended to decrease linearly (P < 0.003) as supplemental lycopene increased from 0 to 200. Control rats fed only basal diet had a greater length of tumors (23.98 mm) than rats fed lycopene supplement groups (12.90 mm and 11.07 mm) (P < 0.05). Moreover tumor length decreased (P < 0.02) and tumor length tended to decrease linearly (P < 0.03) as supplemental lycopene increased from 0 to 200 mg/kg. All tumors showed strong staining with antibodies against mTOR, phospho-S6 and EGER. In conclusion, dietary supplementation with lycopene attenuates the development of renal cell cancers in the predisposed TSC2 mutant Eker rat model. These results suggest that lycopene may play a role in the prevention of RCC. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Renal cell cancer; Lycopene; Eker rat